Interação da matéria de vórtices com estruturas de defeitos em filmes de Nb - Kapp, Juliana Sens Nunes (2009)
In this work we have studied the Vortex Matter dynamics in Nb superconducting films with different arrays of columnar defects. For that we studied the order-disorder line H (T) OD , where the melting of the vortex lattice occurs. The H (T) OD frontier was determined through the imaginary component " of the susceptibility in T measurements, whose peak temperature T Hp is associated with a maximum in energy dissipation, due to the viscous movement of vortices, which signals the beginning of a nonlinear regime. For this study we modified the pinning force efficiency in Nb samples using three different approaches: varying the technique employed to fabricate the defects, using large-value excitation fields and modifying the angle between the columnar defects in the sample and the applied magnetic field. As the pinning efficiency decreases, two regimes in the melting line become detectable, distinguished form each other by the appearance of a kink in a characteristic temperature k T . For temperatures lower than k T , pinning is significantly more efficient, and the H (T) OD line can be adjusted with a power-law; at higher temperatures, depinning is favored by thermal excitation, and the transition line is adjusted by a Bose-glass model for columnar defect systems. In this work we also studied both regimes with these theoretical models, previously available in the literature. For this we built the H T diagram with the irreversibility line irr H , upper critical field C2 H , and the order-disorder line H (T) OD , studying the dependence of the solid-liquid transition with the excitation field, frequency and angle of the applied magnetic field. We compared the pinning forces acting on different samples and applied a universal scaling approach to our experimental data points, proving the adequacy of the model to our results.